PERLINDUNGAN MASYARAKAT SIPIL DALAM KONFLIK BERSENJATA DI MYANMAR BERDASARKAN SUDUT PANDANG HUKUM INTERNASIONAL - Aulia Indra Keumala; Phoenna Ath Thariq (Jurist Argumentum: Pemikiran Intelektual Hukum, 2023)
Myanmar is a country in Southeast Asia whose government is currently being overthrown and controlled by the military. The military junta carried out attacks against civilians, such as massacres against demonstrators and several riots that resulted in the destruction of several state assets and casualties. Myanmar's internal conflicts can be classified as low-intensity conflicts because they are carried out openly and have caused a crisis of legal legitimacy in the region. The purpose of this research id to find out the protection of civil society applied in the armed conflict in Myanmar in International Law and to find out the consewuences of the failure to protect civil society in the armed conflict in Myanmar based on International Law. This research was conducted using a normative research method or library research as a primary material and a study of legal materials in the field as a secondary material for supporting data to be analyzed and explained accurately to the problems studied. The theory used in this study is the theory of state responsibility, the theory of emergencies and the theory of law enforcement. This study found that there were serious violations against civil society in Myanmar and besides that there were several provisions regarding the protection of civilians in a state of conflict, there were preventive rules regarding the possibility of civilian casualties. It is recommended that the state of Myanmar carry out a consensus settlement of the coup in Myanmar by appointing a neutral country that has the power to intervene in the current territory of Myanmar to oversee the transition of power or at least issue a resolution to summon the Myanmar military junta to comply with the applicable conventions so that crimes against humanity do not occur for as long as possible. emergency period in Myanmar.